Potential of Trichosporon asahii against Alternaria sp. and mechanisms of actions - Bosqueiro, Ariane Silva; Bizarria, Rodolfo [UNESP]; Rosa-magri, Márcia Maria (Grupo Paulista de Fitopatologia, 2020)
Alternaria sp. is a fungus that causes rot in several crops, causing damage to the agricultural production chain. Biological control agents constitute an alternative to reduce the use of pesticides in the crops, a social demand for modern agriculture. The aim of the present study is to demonstrate the antagonistic effect of the yeast Trichosporon asahii (3S44) on the mycelial development of Alternaria sp. and some in vitro mechanisms of action. Trichosporon asahii showed antagonistic activity towards Alternaria sp., presenting mycelial inhibition (57.47%). The assays indicated production of volatile organic compounds (VOCs), competition for nutrients, biofilm formation, production of killer toxins and β-1,3-glucanase as mechanisms of action of T. asahii. Collectively, our results showed the potential of T. asahii to control the mycelial development of Alternaria sp. and some mechanisms of action of this yeast for future biotechnological studies.

Alternaria sp. é um fungo que causa podridão em diferentes culturas agrícolas, causando danos a cadeia de produção. Agentes de controle biológico são uma alternativa para reduzir o uso de agrotóxicos nas lavouras, uma demanda social para a agricultura moderna. O objetivo deste trabalho é demonstrar o efeito antagônico da levedura Trichosporon asahii (3S44) no desenvolvimento micelial de Alternaria sp. e alguns dos mecanismos de ação in vitro. Trichosporon asahii apresenta atividade antagônica frente Alternaria sp., com inibição micelial (57,47%). Os ensaios indicaram a produção de compostos orgânicos voláteis (COVs), competição por nutrientes, formação de biofilme, produção de toxina killer e β-1,3-glucanase como mecanismos de ação de T. asahii. Coletivamente, os resultados demonstraram o potencial de T. asahii no controle do desenvolvimento micelial de Alternaria sp. e mecanismos de ação da levedura, para futuros estudos biotecnológicos.
Trichosporon asahii contra Alternaria sp. e mecanismos de ação
Keywords: Antagonism; yeast; biological control; mechanisms of action; Antagonismo; Levedura; Controle biológico; Mecanismos de ação